2021
DOI: 10.1021/acscatal.0c04526
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-Loading Ruthenium Catalysts by Plasma-Enhanced Atomic Layer Deposition for a Solid Oxide Fuel Cell

Abstract: Designing and fabricating highly active and thermally stable catalysts with minimal noblemetal loading is crucial for solid oxide fuel cells that operate with direct methane fuel. In this study, ultralow-loading Ru catalysts (<10 μg cm −2 ) are fabricated using plasma-enhanced atomic layer deposition (PEALD) on a samaria-doped ceria (SDC) backbone for a methane oxidation electrode. The Ru catalyst with a high surface area and a high triple-phase boundary density shows electrochemical performance superior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The complete oxidation of CH 4 to CO 2 in solid oxide fuel cells to generate electricity is also being investigated; however, high operating temperature (300−700 °C), rapid drop in efficiency due to coke deposition, and sulfur poisoning are other unsolved issues. 16,17 Another, approach to utilize methane as a feedstock is thermocatalytic nonoxidative partial dehydrogenation to alkenes and aromatics which requires high temperature. Partial dehydrogenation is advantageous over complete dehydrogenation, as it produces platform chemicals that can be directly used for the chemical synthesis along with hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The complete oxidation of CH 4 to CO 2 in solid oxide fuel cells to generate electricity is also being investigated; however, high operating temperature (300−700 °C), rapid drop in efficiency due to coke deposition, and sulfur poisoning are other unsolved issues. 16,17 Another, approach to utilize methane as a feedstock is thermocatalytic nonoxidative partial dehydrogenation to alkenes and aromatics which requires high temperature. Partial dehydrogenation is advantageous over complete dehydrogenation, as it produces platform chemicals that can be directly used for the chemical synthesis along with hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ALD offers the advantage of reproducibly introducing metal nanocatalysts with high uniformity even on complicated structures and easily depositing composite oxides with diverse compositions. [77][78][79][80][81][82][83][84][85][86] Recently, Tsampas reported an example of successful electrode activity enhancement using ALD by uniformly coating Pt nanocatalysts onto an LSCM electrode (Fig. 8a).…”
Section: Studies Of the Chemical/electrochemical Functionalization Of Electrodesmentioning
confidence: 99%
“…In addition, An et al reported that the plasma-enhanced atomic layer deposition (PEALD) technique can significantly reduce the amount of precious metal usage (2 ~ 100 times) by achieving efficient metal catalyst dispersion compared to the conventional sputtering method. 81 PEALD is a type of ALD that uses plasma as a reactant. It is known to facilitate nucleation in the first few cycles compared to general thermal ALD, providing metal nanocatalysts with high density levels using a very small number of ALD cycles.…”
Section: Studies Of the Chemical/electrochemical Functionalization Of Electrodesmentioning
confidence: 99%
“…reported ultralow (8 nm) loading of ruthenium catalyst on SDC anode for direct methanol solid oxide fuel cells, and compared the performance of electrodes prepared by plasma‐enhanced atomic layer deposition (PEALD) and sputtering technique (Figure 13e). [ 232 ] Where, PEALD technique achieved fine dispersion and ultralow loading (5%) of Ru nanoparticles, while sputtered Ru was not able to penetrate into the pores and build up on top of the SDC columnar structure (Figure 13f). The Ru/SDS anodes achieved 30% higher power density with high thermal density when compared to unmodified SDC structures.…”
Section: Ald In Fuel Cellsmentioning
confidence: 99%
“…The Ru/SDS anodes achieved 30% higher power density with high thermal density when compared to unmodified SDC structures. [ 232 ]…”
Section: Ald In Fuel Cellsmentioning
confidence: 99%